CORRELATION BETWEEN STRESS AND EATING HABIT AND HIPEREMESIS GRAVIDARUM LEVEL II AND III IN BHAYANGKARA HOSPITAL OF MAKASSAR - nurasni nurasni (Stikes Graha Edukasi Makassar, 2019)
Introduction: : Hiperemesis gravidarum is an excessive nausea vomiting in pregnant women caused by the increase of estrogen hormone and Hcg in serum which is frequently found in the first trimester pregnancy less than 6 weeks of gestational age. The research aims to determine the correlation between stress and eating habit and hiperemesis gravidarum level II and III in Bhayangkara Hospital of Makassar. Method: The research design used was cross sectional study with quantitative study. The sample was selected using quota sampling technique consisting of 33 respondents. The data were analyzed using univariate analysis in the form of table frequency and bivariate analysis by means of statistic test with the significant level of p-value=0.05. Results: The results of the two research variables indicate that based on univariate analysis 23 people (69.7%) have stress; 26 people (78.8%) have irregular eating habit, and 25 people (75.8%) have hiperemesis gravidarum level III compared to the respondents having hiperemesis gravidarum level Il consisting of 8 people (24.2%). Based on bivariate analysis using statistic test, it is indicated that there is a significant correlation between stress and eating habit and hiperemesis gravidarum level II and III in Bhayangkara Hospital of Makassar in 2017 with the value of p : 0.000. Discussion: Hiperemesis gravidarum is an excessive nausea vomiting in pregnant women caused by the increase of estrogen hormone and Hcg in serum which is frequently found in the first trimester pregnancy less than 6 weeks of gestational age. Conclusion: The conclusion in this study is that there is a significant relationship between stress and diet with hyperemesis gravidarum levels II and III. Suggestion: Thus, it is suggested that pregnant women avoid stress and irregular eating habit, so hiperemesis gravidarum does not worsen the condition of the first trimester of pregnant women.